Dampak Metode Pembelajaran Pada Siswa Kelas III Sdn 1 Ketitang: Minat Baca - Septianingrum, Vindi (Prosiding University Research Colloquium, 2021)
This This research aims to describe the impact of mindmapping learning methods on students of grade III SDN 1 Ketitang, especially on reading interests. The study took place using descriptive qualitative research and using methods of measuring interview and observation data. The main subject of this study was the students of class III SDN 1 Ketitang consisting of 15 students and 1 teacher. To test the validity of the data in this study used a credibility test of triangulation techniques and triangulation of sources. The results showed that there were differences in the results of students’ reading interest in learning after the application of the mindmapping method. This is evident from the activeness and participation of students in participating in learning activities using the mindmapping method, which is when teachers allow students to explore and find out for themselves the student’s interest in which reading they like.